Pengaruh Religiusitas dan Word of Mouth terhadap Keputusan Berkunjung Wisatawan - Riandy Mardhika Adif; Pandu Vidi Widyastana Suseno; Roni Andespa (SAFE-Network, 2024)
Indonesia is rich in old buildings that are rich in historical value, one of which is the history of the arrival of Islam to Indonesia, and has enormous potential to continue to be developed in the tourism sector, especially religious tourism. Surau Tuo Taram religious tourism is one of the tourist destinations with a religious theme. which contains the grave of Sheikh Ibrahim Mufti, the founder of the first surau in Taram. Surau Tuo Taram religious tourism is much sought after by tourists within and outside the province. Surau Tuo Taram Tourism is located in Taram, Harau District, Limapuluh Kota Regency. Most tourists who visit know about Surau Tuo Taram from Word of Mouth or word of mouth. However, there are still many tourists who go to Surau Tuo Taram just to take photos or just enjoy the calm atmosphere around Surau Tuo. This research aims to determine the influence of religiosity on tourists' decision to visit the Surau Tuo Taram religious tourism site and to determine the influence of word of mouth on tourists' decision to visit the Surau Tuo Taram religious tourism site. This research uses a quantitative approach method using questionnaires and direct observation at Surau Tuo Taram. The results of this research show that the religiosity variable (X1) has a positive and significant effect on tourists' visiting decisions (Y) to the Surau Tuo Taram Payakumbuh religious tourism site. This shows that the level of religiosity has an impact on the decision to visit. The results of research on the Word of Mouth variable (X2) show that Word of Mouth has a positive and significant influence on tourists' visiting decisions (Y) to the Surau Tuo Taram Payakumbuh religious tourism site. This shows that Word of Mouth is the cause of tourists being interested in visiting the Surau Tuo Taram Payakumbuh religious tourism which will then have an impact on the decision to visit.